Oxidative Stress Biomarkers as a Predictor of Stage Illness and Clinical Course of Schizophrenia - Juchnowicz, Dariusz; Dzikowski, Michał; Rog, Joanna; Waszkiewicz, Napoleon; Zalewska, Anna; Maciejczyk, Mateusz; Karakuła-Juchnowicz, Hanna (Frontiers in Psychiatry, 2021)
Pro/antioxidant imbalance has been reported in schizophrenia (SZ). However, the results of studies are inconsistent and usually do not include other factors that are highly affected by oxidative stress (OS).This cross-sectional study aimed to determine the serum levels of OS markers and their potential connection with schizophrenia. The total sample comprised 147: 98 individuals with SZ −47 first-episode (FS) and 49 chronic patients (CS)—and 49 healthy individuals (HC) as a control group. The examination included clinical variables and serum levels of antioxidants and oxidative damage products. The significant changes were observed in concentrations of all examined markers, without any specific direction of the pro/antioxidant balance shift between SZ and HC. In the regression model adjusted for cofounders, catalase: OR = 0.81 (95%CI: 0.74–0.88); glutathione peroxidase: OR = 1.06 (95%CI: 1.02–1.10); total antioxidant capacity: OR = 0.85 (95%CI: 0.75–0.98); oxidative stress index: OR = 1.25 (95%CI: 1.03–1.52); ferric reducing ability of plasma: OR = 0.79 (95%CI: 0.69–0.89); advanced glycation end products: OR = 1.03 (95%CI: 1.01–1.04); and advanced oxidation protein products (AOPP): OR = 1.05 (95%CI: 1.03–1.07) turned out to be significant predictors of schizophrenia. In the multiple stepwise regression model, pro/antioxidant status and their interaction with the duration of illness-related factors affected schizophrenia symptoms: positive symptoms (FRAPxKYN), negative (DITYR, FRAP, CAT), general (KYN), and over-all psychopathology (KYNxNFK). The results confirm differences in serum levels of oxidative biomarkers between SZ patients and healthy individuals. The pro/antioxidant status could be considered a predictor of schizophrenia and the factor affects patients' symptom severity.